On Differential Mechanisms for Underactuated, Lightweight, Adaptive Prosthetic Hands - Gao, Geng; Shahmohammadi, Mojtaba; Gerez, Lucas; Kontoudis, George; Liarokapis, Minas (Frontiers in Neurorobotics, 2021)
Over the last decade underactuated, adaptive robot grippers and hands have received an increased interest from the robotics research community. This class of robotic end-effectors can be used in many different fields and scenarios with a very promising application being the development of prosthetic devices. Their suitability for the development of such devices is attributed to the utilization of underactuation that provides increased functionality and dexterity with reduced weight, cost, and control complexity. The most critical components of underactuated, adaptive hands that allow them to perform a broad set of grasp poses are appropriate differential mechanisms that facilitate the actuation of multiple degrees of freedom using a single motor. In this work, we focus on the design, analysis, and experimental validation of \hlr{a four output geared differential, a series elastic differential, and a whiffletree differential that can incorporate a series of manual and automated locking mechanisms. The locking mechanisms have been developed so as to enhance the control of the differential outputs, allowing for efficient grasp selection with a minimal set of actuators. The} differential mechanisms \hlr{are} applied to prosthetic hands, comparing them and describing the benefits and the disadvantages of each.